Kelestarian Kain Pelangi Tempatan Melalui Rekaan Dan Inovasi Proses Penghasilannya - Mohd. Azhar, bin Samin (University Malaysia Sarawak, UNIMAS, 2015)
The Pelangi cloth is a local traditional textile resulted from its adaptation and assimilation of the tie resist patterned fabric called Bandhani from India with the influenced of local and regional art textiles. In early days the Pelangi cloth were developed and widely used in the ceremony and rituals at the court since the 17th century. The textiles were also used extensively among the local traditional Malay community since the 19th century until the beginning of 20th century. Unfortunately, the industries of the Pelangi cloth began to experience a decline subsequently of the production and the industry of the Block Batik cloth followed by the introduction of the Silk Screen Batik around 1920’s and then became obsolete after 1930’s. During 1960’s to 1970’s, tie and dye textiles were introduced by the West to the rest of the world, including Malaysia. This textile continued to be accustomed among the local textile industry as well as being created as textile course in a few of the institutions of higher learning. The study establish that, the local communities today are less familiar and obscure regarding the aspects of the design, production and speciality of the traditional Pelangi cloth as it became archaic than the other types of local textiles. This research seeks to investigate the questions on the aspects of the design and specialities of the local Pelangi cloth focusing on its background and history. Studies were also established from the reproduction and innovation of the Pelangi cloth affiliated with few other textiles techniques to examine its eficiency. This research was also supported by the practitioner feedbacks experienced from the reproduction of the Pelangi cloth, as well as survey results concerning of the design aspects and the appropriateness of the fabric to be redeveloped for its sustainability. A research framework concept has been developed to illustrate the components in focus of the research. Integrated Triangulation that combine a descriptive, practice base research through observation and survey approach has been used as a research methodology to obtain accurate and comprehensive research data. This research is expected to contribute to the development of knowledge and skills in the design and production of the local Pelangi cloth in particularly, within the field of design education and textile crafts of the local textile industry. Furthermore, hopefully this research will be use as a guide in restoring and expanding the production of the local Pelangi cloth and its sustainability.